2013
DOI: 10.1098/rsob.130051
|View full text |Cite
|
Sign up to set email alerts
|

Correlating efficacy and desensitization with GluK2 ligand-binding domain movements

Abstract: Gating of AMPA- and kainate-selective ionotropic glutamate receptors can be defined in terms of ligand affinity, efficacy and the rate and extent of desensitization. Crucial insights into all three elements have come from structural studies of the ligand-binding domain (LBD). In particular, binding-cleft closure is associated with efficacy, whereas dissociation of the dimer formed by neighbouring LBDs is linked with desensitization. We have explored these relationships in the kainate-selective subunit GluK2 by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 39 publications
1
12
1
Order By: Relevance
“…While elimination of Na + binding invariably disrupts the dimer, as expected (Plested et al 2008;Nayeem et al 2011), mutations to residues forming the anion binding site have varied functional effects. Most mutations do accelerate the rate of desensitization (Plested & Mayer, 2007;Wong et al 2007), but three mutants have been identified where the rate of desensitization is slowed (Nayeem et al 2013). For two of these, sidechain rearrangements can explain the phenotype, but for one mutant (GluK2 R775A), the loss of chloride binding was the only apparent structural change.…”
Section: Ion Binding To the Lbd Dimer Interface In Iglur Subunitsmentioning
confidence: 99%
See 3 more Smart Citations
“…While elimination of Na + binding invariably disrupts the dimer, as expected (Plested et al 2008;Nayeem et al 2011), mutations to residues forming the anion binding site have varied functional effects. Most mutations do accelerate the rate of desensitization (Plested & Mayer, 2007;Wong et al 2007), but three mutants have been identified where the rate of desensitization is slowed (Nayeem et al 2013). For two of these, sidechain rearrangements can explain the phenotype, but for one mutant (GluK2 R775A), the loss of chloride binding was the only apparent structural change.…”
Section: Ion Binding To the Lbd Dimer Interface In Iglur Subunitsmentioning
confidence: 99%
“…For two of these, sidechain rearrangements can explain the phenotype, but for one mutant (GluK2 R775A), the loss of chloride binding was the only apparent structural change. One possible explanation is that the charge balance in the WT receptor tends to destabilize the interface, and the loss of two basic sidechains counteracts this (Nayeem et al 2013).…”
Section: Ion Binding To the Lbd Dimer Interface In Iglur Subunitsmentioning
confidence: 99%
See 2 more Smart Citations
“…The LBD features a binding site for ligands, which can be agonists or antagonists. A number of GluK2 LBDs with bound ligands have been resolved by X-ray crystallography [ 10 , 11 ], providing insight into the movement of the receptor and the selectivity of ligand in the receptor gating [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%